Characterizing direct emissions of perfluoroalkyl substances from ongoing fluoropolymer production sources: A spatial trend study of Xiaoqing River, China. (November 2015) - Shi, Yali; Vestergren, Robin; Xu, Lin; Song, Xiaowei; Niu, Xiameng; Zhang, Chunhui; Cai, Yaqi
Abstract: The spatial trend of perfluoroalkyl substances (PFASs) along Xiaoqing River and its tributaries was studied to characterize isomer profiles and quantify emissions from fluoropolymer (FP) manufacturers in China. Substantially elevated ∑PFAS concentrations downstream of tributary 4 demonstrated that the emissions from this FP manufacturer dominated total riverine discharges. Isomer profiles of perfluorooctanoic acid (PFOA) in water displayed a stepwise increase in percentage branched PFOA downstream of tributary 3 (14.0%) and 4 (22.7%) reflecting the importance of FP sources. Strong positive correlations between PFOA isomers in water downstream of tributary 4 indicated that isomer profiles were conserved from emission sources to the final reservoir. Riverine discharges of PFOA (23–67 t/yr) were in agreement with theoretical emission calculations from FP production (68 t/yr) whereas large discrepancies between the two methodologies were observed for perfluorobutanoic acid and perfluoropentanoic acid. Collectively, this study fills critical knowledge gaps for understanding ongoing global sources of PFASs. Graphical abstract: Highlights: Spatial trends of PFASs in Xiaoqing River, China were investigated. Isomer profiles of ongoing fluoropolymer (FP) sources were characterized. Isomer fractionation effects between water and sediment were studied. Riverine discharges were quantified and compared to theoretical emission estimates. Abstract : Isomer profiles along a spatial transect and quantitative emission calculations were used to characterize a major global emission source of perfluoroalkyl carboxylic acids.